Dynamic recrystallization behaviors of a Mg-4Y-2Nd-0.2Zn-0.5Zr alloy and the resultant mechanical properties after hot compression. (5th May 2016) - Zhang, Zhirou; Yang, Xuyue; Xiao, Zhenyu; Wang, Jun; Zhang, Duxiu; Liu, Chuming; Sakai, Taku
Abstract: The development behaviors of ultrafine grains (UFGs) due to continuous dynamic recrystallization (cDRX) were investigated in hot compression of a Mg-4Y-2Nd-0.2Zn-0.5Zr alloy pretreated in solution and subsequently peak-aging. In the aging sample containing statically precipitated particles (SPPs), the occurrence of cDRX starts to take place at medium to high strains, and finally a stable size of UFGs are fully developed in a whole volume. In the as-solution sample with no SPPs, by contrast, the size of UFGs evolved increases rapidly at lower strains, slowly at medium strains and then finally shows a bimodal distribution in high strain. In the latter, smaller grains accompanying with an incomplete formation of UFGs are developed by any effect of dynamically precipitated particles (DPPs). The microtexture evolved is effectively randomized in the regions of UFGs, leading to the formation of a weaker texture. The tensile elongation of the aging sample, with SPPs and fully developed UFGs, was around 17.4%. This was much higher than that of the as-solution one, with no SPPs and incompletely developed UFGs, that was 11.8%, which might result from the more randomized texture due to fully developed UFGs. Graphical abstract: Highlights: The as-solution (AS) samples contain dynamically precipitated particles (DPPs). The as-aged (AA) samples approach almost full ultrafine grains (UFGs) at high strain. The DPPs have an effect on cDRX of as-solution (AS) samples. The texture of UFGs is randomized irrespective of the AS and AA samples. Tensile elongations to fracture were enhanced about 50% by pre-aging treatment.